Tracing the trail of time. Proceedings from the Second Diachronic Corpora Workshop, de R.Hickey, M. Kytö, I. Lancashire y M.Rissanen (eds.). - Tejada Caller, Paloma (Estudios Ingleses de la Universidad Complutense, 2000)
Sin resumen